Trial of labor after caesarean section in low risk pregnancies: is it risky? - Kehl, Sven; Düster, Hanna; Weiss, Christel; Bader, Simon; Schneider, Michael; Beckmann, Matthias; Dammer, Ulf; Pretscher, Jutta (Archives of Gynecology and Obstetrics, 2024)
Purpose: To evaluate the influence of a previous caesarean section on adverse composite maternal and perinatal outcome in women who attempted a trial of labor. Methods: This historical cohort study analyzed maternal and perinatal outcome in women with otherwise low risk pregnancies at term who underwent a trial of labor after a caesarean section (TOLAC). The primary outcome measure was the adverse composite outcome. Secondary outcome measures were amongst others the caesarean section rate and the mode of vaginal delivery. Results: The adverse composite outcome was more frequently in the previous caesarean section group compared to women with no previous caesarean Sect. (22.3% vs. 15.6%, p < 0.0001). The percentage of caesarean Sect. (15.4% vs. 8.2%, p < 0,0001), uterine rupture (1.0% vs. 0.02%, p < 0.0001), placental abruption (1.1% vs. 0.3%, p = 0.0014), vaginal operative delivery (16.0% vs. 8.6%, p < 0.0001), pH < 7.10 (3.7% vs. 2.5%, p = 0.0151), base excess < -12 (3.2% vs. 2.2%, p = 0.0297), abnormal cardiotocography (22.5% vs. 13.9%, p < 0,0001) and fetal blood analysis (6.2% vs. 2.6%, p < 0.0001) was significantly higher in women with a previous caesarean section. Taking the parity into account, these differences could only been seen in women without a previous vaginal delivery. In parous women with a previous vaginal delivery and a caesarean section in history, the adverse composite did not differ between the groups. Only the rate of pH < 7.1 was higher in women after a caesarean Sect. (4.5% vs. 1.8%, p = 0.0436). Conclusion: Trial of labor after caesarean in otherwise low risk pregnancies is associated with a higher rate of complications especially if there is no history of vaginal delivery.
CRIS-Team Scopus Importer:2024-09-06
Keywords: Caesarean section rate; Composite adverse outcome; Prior caesarean section; TOLAC; Uterine rupture; VBAC